Development Of A Fiber Optic Roughness Measuring System - P. Janasekaran, Shamini (Universiti Sains Malaysia, 2006)
This report represents the development of a fiber optic roughness measuring system. As the main part of my final-year project, I developed a system to measure roughness of surfaces using optical fiber. A lot of researches have been done to get a better view of surface roughness and this is described in detail in this report. Besides that, in this project, I am using transmitter and receiver chip to transmit and receive the light to scan on the surface needed. Light from transmitter is sent out through one of the multimode optical fiber twin pack and received by receiver chip through the other attached optical fiber. The hardware system is made of mild steel and the transmitter and receiver circuits are designed in such a way that can be compatible with the system hardware. The receiver circuit has added on circuits of amplifiers to get the outputs amplified. The methods used and steps taken throughout this project are also explained clearly in this report. The measured outputs are obtained through readings on digital multimeter. The measurement results and explanation for the results obtained are presented in the second last chapter. Finally, the last chapter as the conclusion exposes the overall view of the project and suggestions in order to make the system better besides the future prospect of the project. This is to avoid preventable problems during the implementation and usage of the system.